28 Surgery for infective mitral valve endocarditis: a 10 year single centre experience. (7th October 2015) - Jahangeer, S; Hannan, M; Blake, G; Healy, D; Redmond, M; McGuinness, J; Javadpour, H; Chughtai, ZJ; Nolke, L; McCarthy, J
Abstract : Background: Mitral valve endocarditis is a serious clinical condition with significant morbidity and mortality in which surgical intervention is frequently warranted. A retrospective analysis was conducted of the early outcome of surgical intervention in infective mitral valve endocarditis. Methods: Between January 2004 to December 2014, a total of 52 patients with mitral valve endocarditis were operated on. 32 patients underwent a mitral valve repair and 20 had a mitral valve replacement. The patients' perioperative characteristics, in-hospital complications and 30-day mortality were analysed. Results: The patients age ranged from 21 to 82 years old (mean 56 years, SD 15 years), and 40 patients (76.9%) were males. Pre-operative morbidities included Renal Failure (5 patients, 9.6%), History of Cerebrovascular Accident (6 patients, 11.5%), Diabetes (5 patients, 9.6%) and previous cardiac surgery (8 patients, 15.4%). 6 patients (11.5%) were ventilated prior to surgery and 2 patients (3.8%) required an intra-aortic balloon pump insertion before surgery. The mean Euroscore-II was 18.4. 9 patients (17.3%) were operated on as emergencies and 2 cases (3.8%) considered as salvage procedures. The 30-day mortality following surgery for active mitral valve endocarditis was 13.5% (n = 7). Conclusions: Mitral valve endocarditis is a challenging clinical problem which is associated with significant morbidity and mortality. Mitral valve surgery provides an effective treatment but carries a significant risk, which is largely related to the pre-operative state of the patient. In cases of Mitral valve endocarditis, early referral and discussion by the Heart Team is beneficial in these patients.